The trend of the Romanian migration flow explained by means of statistical models - Daniela Gabriela Cozma; Margareta Bocancia (CES Working Papers, 2019)
Over time, the migration phenomenon developed an interdependence relationship with economic development, political stability and social factors. Starting from this context, this paper aims at studying the Romanian emigration flow according to the country of destination between 1990-2016 and the way in which the gross domestic product per capita (GDP) influenced this emigration flow between 2008-2016. The initial hypothesis was that only certain countries were priority targets of the Romanian emigration flow. In our scientific approach we used EUROSTAT and TEMPO databases. In the first part of the paper we used cluster analyzes to confirm that only certain countries are priority destinations, and in the second part we included a multiple linear regression model to find out if the gross domestic product of the country affects in any way the decision to emigrate.
Keywords: 330; Romanian emigration flow; emigration countries; statistical model